Pre-Operative Management and Its Influence on Maladaptive Behavioural Disorders in Children - Petríková, Z. Adamcová; Kenderessy, P. Kenderessy; Petrík, O. Petrík; Adamec, T. Adamec (International Journal of Pediatrics and Child Health, 2023)
Anaesthetics and their influence on children’s brains have become one of the most discussed problems in paediatric anaesthesiology. The experimental studies on animal models have shown that the anaesthetics used in general anaesthesia should have an influence on neurodegenerative processes, neuroapoptosis and the unregulated death of the neuronal cells in the developing brain. Due to this reality, scientists are trying to discover how to minimize the adverse effects of anaesthesia and revise other alternatives of prevention anaesthesia-induced maladaptive behavioural disorders, especially in children. The paper will present the procedures of preoperative management at a children’s faculty hospital in Banská Bystrica, Slovakia, our working place, and reveal how to minimize the adverse effects of anesthesia presenting in maladaptive behavioural disorders.